Pleomorphic adenoma of the eyelid skin: A series of three atypical cases - Sabrina Bergeron; Hiroaki Ito; Bryan Arthurs; Miguel N. Burnier, Jr (Elsevier, 2020)
Mixed tumour of the skin is a rare entity that was initially described over a century ago. Its terminology has been discussed several times. Other commonly used names are chondroid syringoma or pleomorphic adenoma of the skin. It generally presents as a slow-growing subcutaneous mass and it is most commonly seen on the nose or scalp.Whilst its clinical course is most often uneventful, careful histopathological analysis of these lesions is of importance to monitor possible recurrences and identify possible pre-malignant features. The variability of histopathological findings in mixed tumours of the skin may represent a source of conflict amongst pathologist and other specialists, thus explaining the different terminology for this entity (cutaneous mixed tumour, chondroid syringoma and pleomorphic adenoma of the skin) and it's probable under-representation in the litterature.Herein, we provide a short review on the nomenclature of this disease and describe three cases of mixed tumour of the skin with distinctive histopathological patterns; one vascular, one recurrent and one with atypical cytological features.